A Review of the Optimisation of Photopolymer Materials for Holographic Data Storage. (25th June 2012) - Guo, Jinxin; Gleeson, Michael R.; Sheridan, John T.
Abstract : Photopolymers are very interesting as optically sensitive recording media due to the fact that they are inexpensive, self-processing materials with the ability to capture low-loss, high-fidelity volume recordings of 3D illuminating patterns. We have prepared this paper in part in order to enable the recognition of outstanding issues, which limit in particular the data storage capacity in holographic data storage media. In an attempt to further develop the data storage capacity and quality of the information stored, that is, the material sensitivity and resolution, a deeper understanding of such materials in order to improve them has become ever more crucial. In this paper a brief review of the optimisation of photopolymer materials for holographic data storage (HDS) applications is described. The key contributions of each work examined and many of the suggestions made for the improvement of the different photopolymer material discussed are presented.